2017
DOI: 10.1080/02757206.2017.1281266
|View full text |Cite
|
Sign up to set email alerts
|

Taxing the indigenous: a history of barriers to fiscal inclusion in the Bolivian highlands

Abstract: Following the electoral success of left wing and pro-indigenous President Evo Morales, the indigenous poor in Bolivia find themselves at the centre of a new vision of the state, echoed by a fervent citizenship project to include them as contributing participants in this new Bolivia. The state is working to initiate these hitherto informally employed subjects into an individualised fiscal regime: to make them into "taxpayers." While the highland indigenous population have supported Morales' political project, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, that situation is rapidly changing, with diversifying Indigenous economic activities and states’ fiscal imperatives to stabilize public finances (e.g. Sheild Johansson, 2018). As in the case of economic relations described above, taxation reveals the frictions between Indigenous self-representation and politics and hegemonic representations of indigeneity.…”
Section: Indigenous Lands and Resources Become Investiblementioning
confidence: 99%
“…However, that situation is rapidly changing, with diversifying Indigenous economic activities and states’ fiscal imperatives to stabilize public finances (e.g. Sheild Johansson, 2018). As in the case of economic relations described above, taxation reveals the frictions between Indigenous self-representation and politics and hegemonic representations of indigeneity.…”
Section: Indigenous Lands and Resources Become Investiblementioning
confidence: 99%
“…Tax and taxation has recently experienced a long rebound from early fiscal sociology (Goldscheid, 1958;Schumpeter, 1991Schumpeter, [1919) back into the empirical and theoretical terrain of sociology (Martin, 2008;Martin et al, 2009;Newman & O'Brien, 2011;Williamson, 2017;Zhang, 2020) amid existing and longstanding analysis of tax in disciplines such as law (Brown, 2007;Likhovski, 2007), and growing attention paid in geography (Tapp & Kay, 2019), history (Heaman, 2013(Heaman, , 2017Ogle, 2020;Tillotson, 2017), andanthropology (Björklund Larsen, 2017;Makovicky & Smith, 2020;Sheild Johansson, 2018;. Fiscal sociologists have demonstrated that taxes and tax policies have the capacity to exacerbate and institutionalize inequalities (Martin, 2006;Martin & Prasad, 2014).…”
Section: Tax Inequality and Settler Colonial Legal Regimesmentioning
confidence: 99%
“…Further, what are taxes intended to work toward, from the perspective of both state authorities and citizens who contribute to and seek rightful returns from collective pools of revenue? As anthropologists of taxation have persuasively shown, what citizens expect to materialize through taxes can greatly vary from the fiscal outcomes promoted by the state (Peebles 2012;Roitman 2007;Sheild Johansson 2018). The rightful return helps to focus analytical attention on the broader universe of transfers of which taxes are a part, unraveling a parallel dimension to tax evasion and fiscal disobedience.…”
Section: Concluding Remarks: State God and The Rightful Returnmentioning
confidence: 99%